2019
DOI: 10.1002/ange.201812343
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Nitric Oxide Reduction Activity in Flavo–Diiron NO Reductase: Key Roles of the Second Coordination Sphere

Abstract: The second coordination sphere constitutes a distinguishing factor in the active site to modulate enzymatic reactivity. To unravel the origin of NO‐to‐N2O reduction activity of non‐heme diiron enzymes, herein we report a strong second‐coordination‐sphere interaction between a conserved Tyr197 and the key iron–nitrosyl intermediate of Tm FDP (flavo–diiron protein), which leads to decreased reaction barriers towards N–N formation and N–O cleavage in NO reduction. This finding supports the direct coupling of diir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Nitric oxide (NO) reduction yielding nitrous oxide (N 2 O) triggered by nonheme flavodiiron nitric oxide reductases (FNORs) was reported via the proposed hyponitrite pathway and diferrous dinitrosyl pathway in a biological and biomimetic study. In this article, we demonstrated that electronically localized dinuclear {Fe­(NO) 2 } 10 –{Fe­(NO) 2 } 9 DNIC 1 resembling FNORs serves as an NO trapper to facilitate NO reduction to nitrous oxide (N 2 O). Through the direct reaction of NO­(g) with complex 1 (stoichiometric molar ratio of n NO/complex 1 ( n = 1, 2, 3, 5, and 10)), the simultaneous formation of trans -hyponitrite-bound complex 2 , nitrite-bound complex 3 , and N 2 O was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO) reduction yielding nitrous oxide (N 2 O) triggered by nonheme flavodiiron nitric oxide reductases (FNORs) was reported via the proposed hyponitrite pathway and diferrous dinitrosyl pathway in a biological and biomimetic study. In this article, we demonstrated that electronically localized dinuclear {Fe­(NO) 2 } 10 –{Fe­(NO) 2 } 9 DNIC 1 resembling FNORs serves as an NO trapper to facilitate NO reduction to nitrous oxide (N 2 O). Through the direct reaction of NO­(g) with complex 1 (stoichiometric molar ratio of n NO/complex 1 ( n = 1, 2, 3, 5, and 10)), the simultaneous formation of trans -hyponitrite-bound complex 2 , nitrite-bound complex 3 , and N 2 O was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Two scenarios were proposed for ON–NO bond formation: (a) The hyponitrite pathway involving the addition of exogenous ·NO to a proposed mononitrosyl-bridged (κ 2 -N,O-NO) [Fe­(II)–{Fe­(NO)} 7 ] species forms a putative hyponitrito-bound intermediate . (b) Diferrous dinitrosyl pathway: ON–NO coupling occurs via the dinitrosyl diiron [{Fe­(NO)} 7/8 -{Fe­(NO)} 7/8 ] intermediate to release N 2 O, , where Enemark–Feltham notation is adopted …”
Section: Introductionmentioning
confidence: 99%